2023
DOI: 10.1177/14604582221146719
|View full text |Cite
|
Sign up to set email alerts
|

Chatbot features for anxiety and depression: A scoping review

Abstract: Chatbots can provide valuable support to patients in assessing and guiding management of various health problems particularly when human resources are scarce. Chatbots can be affordable and efficient on-demand virtual assistants for mental health conditions, including anxiety and depression. We review features of chatbots available for anxiety or depression. Six bibliographic databases were searched including backward and forwards reference list checking. The initial search returned 1302 citations. Post-filter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…Over the last few years, as chatbot technology has developed at an alarming rate, with large language models now leading the way, their popularity has increased [ 31 ]. While it is not possible to be specific regarding the content of the chatbot until the focus groups have been completed and analyzed, a content management system will be developed to inform the chatbot development.…”
Section: Methodsmentioning
confidence: 99%
“…Over the last few years, as chatbot technology has developed at an alarming rate, with large language models now leading the way, their popularity has increased [ 31 ]. While it is not possible to be specific regarding the content of the chatbot until the focus groups have been completed and analyzed, a content management system will be developed to inform the chatbot development.…”
Section: Methodsmentioning
confidence: 99%
“…In this scoping review we have reported on 17 existing reviews focusing on chatbots for mental health. The country of the institution of the first author were: Qatar (4 reviews: Abd-Alrazaq et al, 2019, 2021Ahmed et al, 2023), Spain (2 reviews: Otero-González et al, 2024, Pachenco-Lorenzo et al, 2021, England (2 reviews: Gaffney et al, 2019, Ogilvie et al, 2022, USA (2 reviews : Vaidyam et al, 2019: Vaidyam et al, , 2020, Singapore (2 reviews: Jabir et al, 2023;Lim et al, 2022), Australia (Martin & Richmond, 2023), China (He et al, 2023), Germany (Bendig et al, 2022), andMexico (Martínez-Miranda, 2017). The reviews included six to 54 articles.…”
Section: Synthesismentioning
confidence: 99%
“…Interestingly, more of the studies included in the reviews were published from 2018 (134 studies) than before (104 studies) and most of the studies were included in only one review (72%). This can be notably explained by the fact that the focus of the reviews were partly diverging, but also by differences in search strategies and screening processes, and of course that some studies were published after the literature search was carried out for some reviews, or that some later reviews only included recent studies (e.g., Ahmed et al, 2023).…”
Section: Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…Since then, interest has grown particularly in the field of mental health (Abd-Alrazaq et al, 2019;Almalki & Azeez, 2020;Milne-Ives et al, 2020). While many focus on depression or anxiety (Ahmed et al, 2023), others address issues such as suicidal ideation (Dharmapuri et al, 2022), substance abuse (Prochaska et al, 2021) and PTSD (Han et al, 2023). Applications linked to mental health (Ly et al, 2017), self-love (Lee et al, 2019), consciousness (Kumar et al, 2023), and the standard of life (Valtolina & Charlie, 2021) are also included, in addition to those specifically relevant to mood disorders.…”
Section: Introductionmentioning
confidence: 99%